Compression Work of Steel Reinforced Concrete Columns - I. Lapenko, O; V. Shevchenko, O; Masud, N (International Journal of Engineering and Technology, 2018)
The article deals with the calculation of steel reinforced concrete columns compression and verification of local stability in fixed formwork. It is concluded that it is expedient to calculate the total stability for the resulted sections, and when checking local stability â€“ to follow the instructions Eurocode 4. When checking the local stability of steel sheets, working as part of reinforced concrete structures, the Eurocode 4 guidelines should be followed, while taking into account the following requirements: leave out of account on the local stability of the concrete cross-section (the steel profile is completely surrounded by concrete); concrete cross-section (steel profile is completely concrete, partially concrete cross-section), the steel profile is only partially covered with concrete, as well as for other cross-sections of reinforced concrete columns provided by Eurocode 4 with the corresponding ratio d/ t. The calculation method for the given sections in the calculation of the overall stability of compressed steel reinforced concrete elements is the simple stand one that gives satisfactory results. Calculations show that the loss of local stability of a steel sheet that works concurrently with reinforced concrete occurs at stresses greater than the force of flow in a steel sheet.Â Â